Sub-lethal effects of cadmium on the antioxidant defence system of the hydrothermal vent mussel Bathymodiolus azoricus - Company, Rui (2020)
The mussel Bathymodiolus azoricus is one of the most abundant species in the Mid-Atlantic Ridge hydrothermal vents and is continually exposed to the high-temperature venting fluids containing high metal concentrations and enriched in sulphides and methane, which constitute a potential toxic environment for marine species. The aim of this study was to assess the effects of a sub-lethal Cd concentration on the antioxidant defence system of this mussel. B. azoricus were collected at Menez Gwen vent site (37 degrees 51'N, 32 degrees 31'W) and exposed to Cd (50 microg l(-1)) during 24 days, followed by a depuration period of six days. A battery of stress related biomarkers including antioxidant enzymes (superoxide dismutase-SOD, catalase-CAT; glutathione peroxidases-GPx), metallothioneins (MT), lipid peroxidation (LPO) and total oxyradical scavenging capacity (TOSC) were measured in the gills and mantle of B. azoricus. Cd was accumulated linearly during the exposure period in both tissues and no significant elimination occurred after the 6 days of depuration. Antioxidant enzymes activities were significantly higher in the gills. Cyt-SOD, T-GPx and Se-GPx were induced during the experiment but this was also observed in control organisms. Mit-SOD and CAT activities remained relatively unchanged. MT levels increased linearly in the gills of exposed mussels in the first 18 days of exposure. No significant differences were observed between LPO levels of control and exposed mussels. TOSC levels remained unchanged in control and exposed mussels. This suggests that although Cd is being accumulated in the tissues of exposed mussels, MT defence system is enough to detoxify the effect of Cd accumulated in the tissues. Furthermore, other factors besides the presence of Cd are influencing the antioxidant defence system in B. azoricus.